(untitled) (Economic studies journal, 2020)
This study aimed to measure the risks of bank liquidity and to know its impact on the profitability of the Libyan commercial banks, using the data contained in the annual financial reports and approved by the external auditor for the financial period (2007 - 2010) for the study sample represented by three Libyan commercial banks. Ratios of liquidity risk and profitability from the financial statements of the banks under study,the study hypotheses were formulated and tested using the Statistical Package Program (SPSS) version 23.. One of the most important findings of this study is that there is no statistically significant effect of liquidity risk on the profitability of the Libyan commercial banks under study. It also showed that the Libyan commercial banks under study have very high liquidity, which is reflected in the low profitability of these banks, and also these banks employ About a quarter of customer deposits are in the form of loans, and one of the most important recommendations of this study is the need to urge the management of commercial banks to develop tools for measuring and monitoring liquidity risks, re-employ excess liquidity in areas that generate income, maintain a balanced rate of liquidity, and keep pace with the requirements of the Basel Committee.